The study of drug release behaviour from Janus particles for synergistic drug delivery - Lim, Annie (2019)
Janus particles are colloidal particles with more than one type of surface chemistry or composition that shows promising potential as a drug delivery system due to their dual functionally and anisotropic properties. The parameters involved in the production of Janus particles such as stirring speed, temperature and polymer to surfactant ratio are crucial to relating the size of particles to its drug release profiles. This report studies the Janus particle formation in PLLA/EVA polymer combination. The effect of varying stirring speed on the particle size and Janus particles formation was recorded and analysed. Also, the effect of the different sizes of Janus particles produced were further studied for their drug delivery effectiveness. It was observed that by increasing the stirring speed, smaller particles are produced with a decreasing encapsulation efficiency of DOX and increasing encapsulation efficiency of PTX.